Pre-conceptual studies of a travelling wave array antenna for the EAST. (1st March 2023) - Li, Jiahao; Ragona, R; Hillairet, J; Zhang, Wei; Chen, Zhaoxi; Zhang, Xinjun; Yang, Qingxi
Abstract: One of the primary problems of ion cyclotron range of frequency (ICRF) systems in magnetic confinement experiments is the coupling of a large amount of radio frequency wave power through the plasma cut-off layer within the voltage limits of the antenna system. Travelling wave array (TWA) antennas have higher coupling than conventional ICRF antennas, which is manifested in a sharp and optimized k // spectrum. As a pre-study of TWA applications in tokamaks, a TWA antenna with six consecutive straps and double-fin capacitors was conceptually designed for the experimental advanced superconducting tokamak (EAST). The antenna geometry was optimized to seek a low reflection coefficient for EAST ICRF heating scenarios. The design and simulation results of the TWA antenna are briefly presented. The results of the frequency sweep in vacuum show that a bandwidth of approximately 3 MHz with S 11 < −30 dB can be obtained. The peak of the k // power spectrum is adjusted to ∼3–4 m −1 at the frequency of 34–36 MHz. In addition, the properties of the power flow and the characteristics of the wave field are also discussed by modelling the plasma facing the TWA antenna using a cold plasma medium. The results in this study may provide some reference and guidance for the study of TWA antennas and other ICRF antennas in magnetic-confined fusion devices like EAST or the Chinese Fusion Engineering Test Reactor.